2012
DOI: 10.2478/s11658-011-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of P5 ATPase mRNA in the mouse

Abstract: P5 ATPases (ATP13A1 through ATP13A5) are found in all eukaryotes. They are currently poorly characterized and have unknown substrate specificity. Recent evidence has linked two P5 ATPases to diseases of the nervous system, suggesting possible importance of these proteins within the nervous system. In this study we determined the relative expression of mouse P5 ATPases in development using quantitative real time PCR. We have shown that ATP13A1 and ATP13A2 were both expressed similarly during development, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…It is implicated in transportation of a variety of cations across the membrane and it is significantly expressed in a variety of organs, including colon, kidney, liver, intestine, stomach, skeletal muscle and brain [Schultheis et al, ]. Moreover, few studies showed higher levels of this transcript during first stages of mouse development, suggesting that ATP13A3 may be involved in early organogenesis [Weingarten et al, ]. XXYLT1 encodes for an endoplasmic reticulum localized xylosiltransferase, which can transfer a second xylose to different epidermal growth factor (EGF)‐like domains of the Notch protein [Sethi et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…It is implicated in transportation of a variety of cations across the membrane and it is significantly expressed in a variety of organs, including colon, kidney, liver, intestine, stomach, skeletal muscle and brain [Schultheis et al, ]. Moreover, few studies showed higher levels of this transcript during first stages of mouse development, suggesting that ATP13A3 may be involved in early organogenesis [Weingarten et al, ]. XXYLT1 encodes for an endoplasmic reticulum localized xylosiltransferase, which can transfer a second xylose to different epidermal growth factor (EGF)‐like domains of the Notch protein [Sethi et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…A mutational screening of this gene also detected a missense variant (p.Glu646Asp) in 6 out of 32 individuals affected by ASD, although the pathogenicity of this variant remains unclear [Kwasnicka‐Crawford et al, ]. The neuronal functions of ATP13A4 have not been investigated yet, but ATP13A4 expression in mice increases during neurogenesis suggesting that it might be critical in early neuronal development [Vallipuram et al, ; Weingarten et al, ]. Overexpressing ATP13A4 in a cell line causes an increase in intracellular calcium, and the p.Glu646Asp amino acid change identified in subjects with ASD suppresses such effect [Vallipuram et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Two standard housekeeping control genes, phosphoglycerate kinase 1 (PGK1) and hypoxanthine phosphoribosyl transferase ( HPRT ), were used (Wong et al ., ). The expression of PGK1 and HPRT has been verified to be stable during development (Weingarten et al ., ). We validated the expression of three genes in the Taconic mice: myelin transcription factor 1 like ( MYT1L ), glyoxalase 1 ( GLO1 ) and dishevelled associated activator of morphogenesis 1 ( DAAM1 ).…”
Section: Methodsmentioning
confidence: 97%